Histology-verified myocardial fibrosis and quantification in severe AS patients: correlation with non-invasive LV myocardial tissue assessment. (3rd October 2022) - Maltes, S; Abecasis, J; Pinto, D G; Santos, R R; Oliveira, L; Mendes, G S; Guerreiro, S; Lima, T; Freitas, P; Ferreira, A; Ramos, S; Felix, A; et al.
Abstract: Background: Myocardial fibrosis (MF) is a common finding and a potential adverse prognostic marker in several cardiac diseases, including in severe aortic stenosis (AS). While histological analysis obtained through endomyocardial biopsy remains the gold-standard for MF assessment, non-invasive cardiac imaging may offer surrogate biomarkers for fibrosis. We tried to assess the correlation between MF quantification at histopathology and cardiac magnetic resonance (CMR)-derived tissue characterization data in patients with severe AS. Methodology: Single-center prospective cohort enrolling 71 patients with severe symptomatic high-gradient AS undergoing surgical aortic valve replacement (SAVR) (mean age 71±9 years; 49% male, mean valvular transaortic gradient 60±20 mmHg; mean left ventricle [LV] ejection fraction 58±9%). Those with past history of myocardial infarction or cardiomyopathy were excluded. All patients underwent pre-operative CMR study with LV tissue characterization and quantification. Normal T1 mapping value was defined as >1021ms as per center protocol. Myocardial tissue was obtained during SAVR either through myocardial biopsy at basal LV septum or harvested from surgical myectomy specimens. Masson's trichrome stain was used for collagen/fibrosis assessment. Automatic quantification was obtained at QuPathTM digital pathology software after applying a dedicated artificial intelligence algorithm on ultra-high-resolution digital slide scanning images. Results: Histology-confirmed MF was observed in all patients (median percentage of fibrotic myocardial tissue 15% [IQR 9–22%]). Median global T1 mapping and extracellular volume (ECV) percentage was 1048ms (IQR 1027–1078) and 24% (IQR 20–30%), respectively. Late gadolinium enhancement (LGE) with a non-ischemic pattern was present in 42 patients (59%) with a median LGE mass of 5.8g [IQR 1.0–10.2]; median percentage of 3.7% [IQR 0.6–10.4]. While neither T1 mapping (global or basal LV septum), ECV nor LGE had any significant correlation with histology-confirmed MF (Figure 1) the vast majority had significantly elevated global and basal LV septum T1 mapping – 81% and 92%, respectively. Conclusion: In this single-center prospective study, microscopic MF was present in all patients with severe symptomatic high-gradient AS, was accompanied by elevated T1 mapping values but no correlation was found between myocardial fibrosis at histopathology analysis and CMR-derived LV tissue characterization parameters. This may not only stem from sampling (single point biopsy vs. whole myocardial tissue assessment) but also from distinct evaluation of different types of fibrosis by different methods. Funding Acknowledgement: Type of funding sources: None.